Single Leg Depth Jump Kombinasi Core Plank Knee To Elbow Terhadap Power Otot Tungkai Atlet - Triyanita, Maya; Dwi Tirta, Siti Sardianti (Jurnal Fisioterapi Terapan Indonesia, 2023)
Power limit training is defined as the movement to get a jump on athletes in doing the maximum jump smash. Badminton requires leg muscle explosive power because it is the muscle's ability to overcome loads and with a high speed of contraction. This study aims to determine the effect of the single leg depth jump exercise, the combination of the knee to elbow core plank, on increasing leg power in badminton athletes. This study uses an experimental design method. This research was conducted on badminton athletes using a total sampling technique of 13 people, namely the Pliometric Simgle Leg Dept Jump Combination Core Plank Knee To Elbow treatment and each group was given exercise 3 times a week for 6 weeks. Measurement of leg muscle power in badminton athletes with the Vertical Jump Test. The research value showed an increase in leg muscle power where the pre-test mean value was 36.46 ± 9.00 increased to 45.54 ± 9.28 during the post test and obtained a value of p = 0.000. It is concluded that the provision of the Plyometric Single Leg Depth Jump combination of Core Plank Knee for Elbow can increase leg muscle power for badminton athletes. Latihan power tungkai didefinisikan sebagai gerakan untuk memperoleh lompatan pada atlet dalam melakukan jump smash yang maksimal. Bulu tangkis membutuhkan daya ledak otot tungkai karena merupakan kemampuan otot untuk mengatasi beban dan dengan kecepatan kontraksi yang tinggi. Penelitian ini bertujuan untuk mengetahui pengaruh latihan singgle leg depth jump kombinasi core plank knee to elbow terhadap peningkatan power tungkai pada atlet bulu tangkis. Penelitian ini menggunakan metode experimen design. Penelitian ini dilaukan pada atlet bulu tangkis dengan menggunakan teknik total sampling sebanyak 13 orang yaitu diberikan perlakuan latihan Pliometrik Simgle Leg Dept Jump Kombinasi Core Plank Knee To Elbow dan masing-masing kelompok diberikan latihan 3 kali seminggu selama 6 minggu. Pengukuran power otot tungkai pada atlet bulu tangkis dengan Vertical Jump Test. Nilai penelitian menunjukan peningkatan power otot tungkai dimana nilai rerata pre test 36,46±9,00 meningkat menjadi 45,54±9,28 saat post test dan didapatkan nilai p=0.000.Disimpulankan pemberian latihan Pliometrik Singgle Leg Depth Jump kombinasi Core Plank Knee To Elbow dapat meningkatkan power otot tungkai untuk atlet bulu tangkis.